Comprehensive analysis of miRNome alterations in response to sorafenib treatment in colorectal cancer cells - Pehserl, Anna-Maria; Scheideler, Marcel (International journal of molecular sciences, 2016)
MicroRNAs (miRNAs) are master regulators of drug resistance and have been previously proposed as potential biomarkers for the prediction of therapeutic response in colorectal cancer (CRC). Sorafenib, a multi-kinase inhibitor which has been approved for the treatment of liver, renal and thyroid cancer, is currently being studied as a monotherapy in selected molecular subtypes or in combination with other drugs in metastatic CRC. In this study, we explored sorafenib-induced cellular effects in Kirsten rat sarcoma viral oncogene homolog olog (KRAS) wild-type and KRAS-mutated CRC cell lines (Caco-2 and HRT-18), and finally profiled expression changes of specific miRNAs within the miRNome (>1000 human miRNAs) after exposure to sorafenib. Overall, sorafenib induced a time- and dose-dependent growth-inhibitory effect through S-phase cell cycle arrest in KRAS wild-type and KRAS-mutated CRC cells. In HRT-18 cells, two human miRNAs (hsa-miR-597 and hsa-miR-720) and two small RNAs (SNORD 13 and hsa-miR-3182) were identified as specifically sorafenib-induced. In Caco-2 cells, nine human miRNAs (hsa-miR-3142, hsa-miR-20a, hsa-miR-4301, hsa-miR-1290, hsa-miR-4286, hsa-miR-3182, hsa-miR-3142, hsa-miR-1246 and hsa-miR-720) were identified to be differentially regulated post sorafenib treatment. In conclusion, we confirmed sorafenib as a potential anti-neoplastic treatment strategy for CRC cells by demonstrating a growth-inhibitory and cell cycle-arresting effect of this drug. Changes in the miRNome indicate that some specific miRNAs might be relevant as indicators for sorafenib response, drug resistance and potential targets for combinatorial miRNA-based drug strategies.